The Importance Of A Linguopragmatic Approach In Translating Advertising Texts - Gafurova, Mutabar (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The article explores the theoretical and practical significance of a linguo-pragmatic approach in translating advertising texts. It emphasizes that a translator’s task is not merely literal translation, but the recreation of the message’s pragmatic force, emotional impact, and cultural adaptation in the target environment.